Release of Chlorine during Mallee Bark Pyrolysis - Rahim, M.; Gao, Xiangpeng; Garcia-Perez, M.; Li, Yi; Wu, Hongwei (American Chemical Society, 2013)
Mallee bark (75-150 µm) was pyrolyzed at 400-900 °C under various conditions to investigate chlorine (Cl) release and distribution among char, tar, and gas. All Cl species in the bark are in form of water-soluble chlorides. In a fixed-bed pyrolysis reactor, the release of Cl is insensitive to pyrolysis temperature between 400 and 900 °C, with Cl completely released with volatiles (~77% in tar and ~23% in gas). In a drop-tube/fixed-bed reactor, under continuous feeding, the amount of Cl released at 400 °C is similar to that in the fixed-bed reactor. However, Cl retention in char increases with temperature, reaching a maximum at 600 °C (~42%), and then decreases with further temperature increases (e.g., only ~6% at 900 °C). In the same drop-tube/fixed-bed reactor under pulsed feeding conditions, Cl release and distribution follow similar trends but to a lesser extent. The results confirm that volatile-char interactions also play important roles in Cl release and distribution among products during biomass pyrolysis and that Cl in char is thermally unstable at elevated temperatures. Calculations by difference further suggest that substantial Cl (47-84%) is present in tars. Quantification of Cl in tar was then carried out experimentally via in situ combustion of biomass volatiles produced using a two-column pyrolysis/combustion reactor.The results confirm the presence of substantial organically bounded Cl in tar. The mass balances of Cl in char, tar, and gas achieve ~100% closure during biomass pyrolysis in the fixed-bed reactor between 400 and 900 °C, as well as that during biomass pyrolysis in the drop-tube/ fixed-bed reactor below 600 °C. However, at temperatures >600 °C, 100% Cl mass balance cannot be achieved during in situ combustion of volatiles and the data suggest that some Cl react with inorganic species (e.g., Na and K) in the gaseous phase to form alkali chlorides, which are deposited on the reactor wall.